Potential scour for marine current turbines based on experience of offshore wind turbine - Chen L.; Lam W.H.; Shamsuddin A.H. (Institute of Physics Publishing, 2023)
The oceans have tremendous untapped natural resources. These sources are capable to make significant contribution to our future energy demands. Marine current energy offers sustainable and renewable alternative to conventional sources. Survival problems of Marine Current Turbines (MCTs) need to be addressed due to the harsh marine environment. The analogous researches in wind turbine have been conducted. Some of the results and knowledge are transferable to marine current energy industry. There still exist some gaps in the state of knowledge. Scour around marine structures have been well recognised as an engineering issue as scour is likely to cause structural instability. This paper aims to review different types of foundation of MCTs and potential scour and scour protection around these foundations based on the experience of offshore wind turbine farm. Published under licence by IOP Publishing Ltd.